Analyzing model uncertainty and economies of scale of the Swedish national freight model to changes in transport demand - Westin, Jonas; Vierth, Inge; Jong, Gerard de; Karlsson, Rune; Krüger, Niclas A.; Johansson, Magnus (European Journal of Transport and Infrastructure Research, 2016)
The purpose of the paper is to analyze model uncertainty and economies of scale of the Swedish national freight transport model system Samgods to changes in its zone-to-zone base matrices. Even though economies of scale is important for freight transport, few studies analyze model uncertainty and economies of scale at a national level. Compared to many large scale networkbased freight models working on aggregated transport flows, an important feature in Samgods is that it simulates logistics behavior at a disaggregated firm level. The paper studies effects on total tonne- and vehicle-kilometre, modal split, consolidation and logistics costs when the base matrices are scaled up and down and estimates economies of scale for Swedish freight transports. The results indicate that the logistics model can find new logistics solutions for larger demand volumes, mainly by shifting freight to sea transport. If transport volume increases with one percent, average logistics cost per tonne is reduced by around 0.5 percent. Part of the cost reduction comes from increased consolidation of shipments due to larger transport volumes. The results derived in the paper can serve as a reference for empirical validation and comparisons with other large scale freight models. The paper is a first contribution that tries to fill the knowledge gap on the impact of base matrices on transport model outcomes, such as economies of scale, in the context of a full-fledged real-world freight transport model.